2016
DOI: 10.1007/s40145-016-0205-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different backbone binders on the characteristics of zirconia parts using wax-based binder system via ceramic injection molding

Abstract: Abstract:In this work, various backbone binders were used in wax-based binder system to formulate zirconia parts by ceramic injection molding (CIM). The effect of different backbone binders on the molding, debinding, and sintering behaviors was investigated. After blending process, the feedstock using multi-polymer components exhibited more homogeneous structure compared with that using the mono-polymer ones due to the synergistic effect of multi-polymers. During solvent debinding, some defects such as "slumpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The same effect was obtained by Jiaxin Wen and collaborators for kerosene. The observed cracking was explained by them as result of EVA large volume swelling during solvent debinding [ 20 ]. On the basis of this information, the swelling effect of the EVA copolymer in heptane was tested.…”
Section: Resultsmentioning
confidence: 99%
“…The same effect was obtained by Jiaxin Wen and collaborators for kerosene. The observed cracking was explained by them as result of EVA large volume swelling during solvent debinding [ 20 ]. On the basis of this information, the swelling effect of the EVA copolymer in heptane was tested.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, Wen et al obtained zirconia relative densities of 97.4%, 97.5%, and 98.6% for feedstocks respectively based on HDPE, PP, and HDPE/PP backbone binders [ 33 ]. They concluded that multi-polymer-based feedstocks presented higher densification ability.…”
Section: Resultsmentioning
confidence: 99%
“…Wen et al employed EVA, PP, LDPE, HDPE, and their blends as backbone binders in feedstocks containing paraffin wax as plasticizer [ 33 ]. Using scanning electron microscopy and deviation of density, they concluded that feedstocks composed of multiple backbone binders, such as LDPE/HDPE or PP/HDPE, present the more homogenous structure after mixing, leading to the highest densification ability.…”
Section: Introductionmentioning
confidence: 99%
“…The next stage is the process of pouring the finished mold with liquid metal and cleaning the resulting casting [1][2][3][4]. In the industry, for the described technology, there is a large variety of model masses, which are mostly waxes [5][6][7][8][9][10]. Chakravorty et al [13] proposed the division of waxes into three groups: natural waxes (waxes from bees, candelilla, carnauba, rice, cane), hydrocarbon waxes (ozocerite, ceresin, paraffine), and synthetic waxes (resins, amide, castor wax), as well as unfilled waxes and filled waxes, which, despite being non-Newtonian liquids [14], usually show similar behavior.…”
Section: Introductionmentioning
confidence: 99%
“…However, it cannot be used again for the production of the model mass because there is a danger that it contains particles of foreign materials or ceramic mass. This may lead to unevenness on the surface of the model or to other surface defects, which can cause shortcomings [4,10,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%